แนวทางเสริมสร้างศักยภาพวิสาหกิจชุมชนในจังหวัดสระแก้ว ผ่านกระบวนการมีส่วนร่วมของชุมชน : กรณีศึกษาวิสาหกิจชุมชนจักสานและผ้าทอ - วิศวธีรานนท์, อัมพวัลย์; ภู่ทอง, พิศรวัส; มหิงษ์, มนศักดิ์ (วารสารศรีนครินทรวิโรฒวิจัยและพัฒนา สาขามนุษยศาสตร์และสังคมศาสตร์, 2020)
การวิจัยแบบมีส่วนร่วมนี้ มีวัตถุประสงค์เพื่อหาแนวทางเสริมสร้างศักยภาพวิสาหกิจชุมชนจักสานและผ้าทอในจังหวัดสระแก้ว ซึ่งกลุ่มเป้าหมาย คือ ผู้มีส่วนได้ส่วนเสียกับการดำเนินงานด้านวิสาหกิจชุมชนในจังหวัดสระแก้ว ตั้งแต่พุทธศักราช 2557-2561 จำนวน 30 คน แบบสัมภาษณ์กึ่งโครงสร้าง เป็นเครื่องมือในการวิจัย ผลการวิจัยพบว่า แนวทางเสริมสร้างศักยภาพวิสาหกิจชุมชน ประกอบด้วย 1) จัดกระบวนการการรวมกลุ่มของชุมชน โดยปรับกระบวนการคิดจากการทำงานคนเดียวมาสู่การรวมกลุ่มกัน เพื่อให้มีกำลังพลในการพัฒนากลุ่มให้เข้มแข็ง และหาแนวทางที่เหมาะสมเพื่อเป็นสิ่งจูงใจให้สมาชิกดำเนินงานต่อเนื่องและสม่ำเสมอ 2) สร้างกิจกรรมการเรียนรู้ของชุมชน โดยการศึกษาดูงานที่สอดรับกับบริบทของชุมชน และจัดกิจกรรมการเรียนรู้ให้มีชีวิต โดยฝึกปฏิบัติกับเยาวชนกลุ่มเล็ก ๆ ในชุมชนให้เกิดแรงบันดาลใจในการสืบสานภูมิปัญญาท้องถิ่นและศิลปวัฒนธรรมไทย 3) จัดการวิสาหกิจชุมชนแบบมีส่วนร่วม เป็นเครือข่ายที่มีคณะกรรมการบริหารแบบยืดหยุ่นตามบริบทของชุมชน สร้างอัตลักษณ์ของผลิตภัณฑ์ทั้งระดับอำเภอและจังหวัด จัดตั้งชมรมจักสาน/การทอผ้าในโรงเรียนระดับอำเภอซึ่งมีทั้งกลุ่มผู้สูงอายุและเยาวชนโดยภาครัฐให้การสนับสนุน และจัดระบบการเงินให้โปร่งใส สมาชิกมีส่วนร่วม/เป็นหุ้นส่วน 4) นำเทคโนโลยีมาใช้ในกระบวนการผลิต/นวัตกรรม เพื่อให้เกิดการรับรองมาตรฐาน โดยเน้นความคิดสร้างสรรค์ผลงานเพื่อเพิ่มมูลค่าของผลิตภัณฑ์ สืบสานลวดลายผ้าทอแบบดั้งเดิมและสร้างสรรค์ลายใหม่ สร้างสรรค์ผลิตภัณฑ์ที่หลากหลายในด้านประโยชน์ใช้สอยด้วย และ 5) นำสื่อสังคมออนไลน์มาใช้เพื่อเพิ่มช่องทางการจัดจำหน่ายผลิตภัณฑ์ของชุมชน โดยสร้างสื่อผ่านโทรศัพท์มือถือที่เป็นเรื่องราวและผลกระทบของผลิตภัณฑ์ที่ทำให้เศรษฐกิจของชุมชนดีขึ้น มีช่องทางการจำหน่ายทั้งศูนย์รวมผลิตภัณฑ์ของชุมชนและการขายตรงผ่านสื่อสังคมออนไลน์ อีกทั้งมีการให้บริการหลังการขายหรือข้อแนะนำผลิตภัณฑ์ระหว่างการใช้งาน และจัดระบบการชำระเงินหลากหลายช่องทาง คำสำคัญ: วิสาหกิจชุมชน จักสาน ผ้าทอ สระแก้ว This participation research had the objective to find guidelines to enhance the potentiality of wickerwork and woven fabric community enterprise in Sakaeo Province. The target group was the 30 concerned persons of the management of Sakaeo community enterprises from B.E. 2557-2561 applied by a semi-structured interview as research instrument. The research study was found out as follows. Channel to reinforce potentiality of community enterprise consisted of 1) Arranging process of community aggregation by adjusting thought process from single working to collective working group in order to acquire manpower to enable more strength to the group. Moreover, appropriate motivation should be provided continuously and regularly to the member. 2) Creating activity of learning to the community namely observation study trip that is in conformity with the community context and arranging activity of learning to small group of youth in the community in order to inspire carrying forward the local wisdom, Thai art and culture. 3) Applying participation to community enterprise management which is the network that its committee manages in a flexible way according to context of the community, creates identity of products both at district level and provincial level, setting up wickerwork/weaving club in provincial schools comprises of aged and youth members under the support of government sector, and managing transparent financial system with participation and partnership of members. 4) Applying technology onto the production /innovation process in order to obtain product standardization by focusing on creative thinking to increase value added products. This is not only to carry forward traditional design and create new design of product, but it is also to enhance diversified utilities of products. 5) Applying social media and releasing the story and the effect of products that can improve economic of the community via mobile phone in order to increase distribution channel of community products. Moreover, allocation of distribution channel at the Center of community products and direct sale via social media, after sale service or suggestion of product application during using the product, including managing several channels of payment should be provided. Keywords: Community Enterprise, Wickerwork, Woven Fabric, Sakaeo